New properties of conformable derivative - Atangana, Abdon; Baleanu, Dumitru; Alsaedi, Ahmed (Open mathematics (Warsaw, Poland), 2015)
Recently, the conformable derivative and its properties have been introduced. In this work we have investigated in more detail some new properties of this derivative and we have proved some useful related theorems. Also, some new definitions have been introduced.